DYE REMOVAL FROM TEXTILE WASTEWATER BY COAGULATION USING ALUM AND PAC - Nada N. Abdul-Razzaq (Journal of Engineering, 2011)
Removal of solar brown and direct black dyes by coagulation with two aluminum based coagulants was conducted. The main objective is to examine the efficiency of these coagulants in the treatment of dye polluted water discharged from Al-Kadhymia Textile Company (Baghdad-Iraq). The performance of these coagulants was investigated through jar test by comparing dye percent removal at different wastewater pH, coagulant dose, and initial dye concentration. Results show that alum works better than PAC under acidic media (5-6) and PAC works better under basic media (7-8) in the removal of both solar brown and direct black dyes. Higher doses of PAC were required to achieve the maximum removal efficiency under optimum pH conditions for both dyes. It was observed that under optimum conditions of pH and dose values, PAC was significantly higher dye removal efficiency than alum for all dyes initial concentrations.